High levels of soluble MICA are significantly related to increased disease‐free and disease‐specific survival in patients with cervical adenocarcinoma. Issue 6 (14th April 2015) - Samuels, S.; Ferns, D. M.; Meijer, D.; van Straalen, J. P.; Buist, M. R.; Zijlmans, H. J.; Kenter, G. G.; Jordanova, E. S.
Abstract Downregulation of major histocompatibility complex class I chain‐related molecule A (MICA) and upregulation of human leukocyte antigen G (HLA‐G) on the tumor cells are important immune escape mechanisms for different epithelial tumors. In addition, upregulation of the soluble forms of the latter molecules in serum leads to peripheral T‐cell and natural killer (NK)‐cell tolerance. As for cervical cancer, it remains unknown whether soluble MICA (sMICA) and soluble HLA‐G (sHLA‐G) concentrations are related to tumor characteristics or patient survival rates. We measured sMICA and sHLA‐G in pre‐treatment sera of a large cohort of cervical cancer patients (n = 366) by enzyme‐linked immunosorbent assay (ELISA). We detected a median sMICA of 174.73 pg/ml and a median sHLA‐G of 5.35 U/ml. We did not find an association between sHLA‐G levels and clinicopathological characteristics. In adenocarcinoma, low sMICA concentration was positively related to recurrent disease, a higher International Federation of Gynecology and Obstetrics (FIGO) stage and vaginal involvement (Mann–Whitney U‐test; P = 0.018, P = 0.042 and P = 0.013, respectively). In the latter patient group, high sMICA levels were associated with better disease‐free survival (DFS) and disease‐specific survival (DSS) (P = 0.011 and P = 0.047). After adjusting for confounding factors, high sMICA proved to be an independent predictor for a better DFS and DSS [HR 0.16; 95% confidence interval (CI) 0.04–0.64; P = 0.009 and HR 0.12; 95% CI 0.03–0.50; P = 0.004]. sHLA‐G did not influence survival in cervical cancer patients, regardless of histology. We conclude that cervical adenocarcinoma patients with high sMICA levels have an increased DFS and DSS. This data warrants a prospective trial to study the functional role of sMICA in cervical adenocarcinoma.